2021
DOI: 10.2147/ijgm.s310677
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Serum Amyloid A in the Diagnosis and Management of Ankylosing Spondylitis

Abstract: Objective The present study aimed to explore the clinical value of serum amyloid A (SAA) in the diagnosis, treatment, and assessment of ankylosing spondylitis (AS). Methods Seventy-eight patients with AS were enrolled as the case group, while the control group consisted of 80 healthy individuals enrolled during the same time period. According to the criteria of the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), patients in the case group were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Moreover, in a recent study, ESR was shown to be a strong predictor of mortality from coronary heart disease and appears to be a marker for aggressive forms of the disease [ 7 , 8 ]. Thus, ESR has a diagnostic value in some conditions and allows monitoring of therapeutic interventions in others [ 9 , 10 ]. It also responds to surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a recent study, ESR was shown to be a strong predictor of mortality from coronary heart disease and appears to be a marker for aggressive forms of the disease [ 7 , 8 ]. Thus, ESR has a diagnostic value in some conditions and allows monitoring of therapeutic interventions in others [ 9 , 10 ]. It also responds to surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen studies were conducted in Asia [ 41 , 42 , 44 46 , 48 , 50 , 55 , 57 , 59 61 , 65 69 , 72 ], six in Europe [ 52 54 , 58 , 62 , 64 ], five in America [ 47 , 49 , 51 , 56 , 70 ], two in Africa [ 63 , 71 ], and one in Oceania [ 43 ]. Thirteen study comparators included patients with RA [ 42 , 43 , 47 , 49 , 52 , 55 , 56 , 63 , 65 , 67 , 71 ], five with SLE [ 45 , 46 , 55 , 58 ], five with FMF [ 53 , 57 , 59 , 60 , 66 ], three with Takayasu arteritis (TA) [ 48 , 61 , 69 ], two with AS [ 44 , 68 ], two with SSc [ 54 , 62 ], two with osteoarthritis (OA) [ 52 , 55 ], one with BD [ 41 ], one with Henoch–Schönlein purpura (HSP) [ 50 ], one with spondylarthritis (SpA) [ 51 ], one with polymyalgia rheumatica (PMR) [ 64 ], one with PsA [ 70 ], and one with gout [ 72 ]. Mean RD duration was reported in 14 studies and ranged between 2.7 and 21.7 years [ 43 ...…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias was considered low in 25 studies [ 42 50 , 52 , 56 63 , 65 , 66 , 68 72 ] and moderate in the remaining seven [ 41 , 51 , 53 55 , 64 , 67 ] (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…8 Furthermore, the study by Yarur et al, 9 In terms of CRP and SAA levels, there was a statistically substantial distinction between the tested groups (p0.001). 9 Hu et al, 14 The levels of SAA were considerably higher in the active group than the inactive group. In agreement with the present results…”
Section: Discussionmentioning
confidence: 95%